Disleksia dalam Pembelajaran Fiqih: Problematika dan Pendekatan Solutif di MI Miftahul Ulum Sumur Tengah - Muhrifah, Muhrifah; Ruslan, Ruslan (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
Learning difficulties or learning disability, also known as learning disorder, is a disorder that makes it difficult for the individual concerned to carry out learning activities effectively. Dyslexia is a disorder of ability and difficulty that has an effect on the learning process, including disorders in the process of reading, speaking, writing and sometimes it is difficult to provide codes (coding) numbers or letters. Fiqh subjects, in this case starting from madrasah ibtidaiyah, need to be implemented correctly. In reality in the field, especially madrasah ibtidaiyah teachers have not been able to overcome the problems that occur. The purpose of this study is to describe: dyslexia problems in Fiqh subjects for students of grade I MI Miftahul Ulum Sumur Tengah. solutions used in overcoming dyslexia problems in Fiqh subjects for students of grade I MI Miftahul Ulum Sumur Tengah. The approach used in this study is a qualitative approach with the type of case study, namely describing the case of a group, which in the research uses interview, observation and documetry methods. The data analysis used is using data reduction, data presentation and drawing conclusions. The validity of the data is using triangulation techniques and time triangulation. Dyslexia problems in Fiqh subjects for students of grade I MI Miftahul Ulum Sumur Tengah. Dyslexia or learning disability is often referred to as learning disorder or learning difficulty is a disorder that makes it difficult for the individual concerned to carry out learning activities effectively